Evaluation of Hepatotoxicity with Treatment Doses of Flucytosine and Amphotericin B for Invasive Fungal Infections. (2nd February 2016) - Folk, Alexandra; Cotoraci, Coralia; Balta, Cornel; Suciu, Maria; Herman, Hildegard; Boldura, Oana Maria; Dinescu, Sorina; Paiusan, Lucian; Ardelean, Aurel; Hermenean, Anca
Abstract : Invasive fungal infection is a well-known cause of morbidity and mortality in immunocompromised patients. In this study we aimed to evaluate the hepatotoxicity induced by combined therapy of flucytosine and amphotericin B, at three different doses administered to mice for 14 days: 50 mg/kg flucytosine and 300 μ g/kg amphotericin B; 100 mg/kg flucytosine and 600 μ g/kg amphotericin B; 150 mg/kg flucytosine and 900 μ g/kg amphotericin B. Liver injuries were evaluated by analysis of optic and electron microscopy samples, changes in TNF- α, IL-6, and NF- κ B inflammation markers levels of expression, and evaluation of mRNA profiles. Histological and ultrastructural analysis revealed an increase in parenchymal and portal inflammation in mice and Kupffer cells activation. Combined antifungal treatment stimulated activation of an inflammatory pathway, demonstrated by a significant dose-dependent increase of TNF- α and IL-6 immunoreactivity, together with mRNA upregulation. Also, NF- κ B was activated, as suggested by the high levels found in hepatic tissue and upregulation of target genes. Our results suggest that antifungal combined therapy exerts a synergistic inflammatory activation in a dose-dependent manner, through NF- κ B pathway, which promotes an inflammatory cascade during inflammation. The use of combined antifungal therapy needs to be dose limiting due to the associated risk of liver injury, especially for those patients with hepatic dysfunction.